Distribution and Abundance of Pila globosa in Biltongi, Natore, Bangladesh - Shathi, Umme Habiba; Hasan, Md. Rashidul; Rahman, Md. Redwanur (Journal of Sustainability and Environmental Management, 2023)
Freshwater snail population numbers and their ecological significance need to be better understood. This study aimed to measure snail abundance in Biltongi-Narayanparabeel in the Natore district. The objective was to establish the population density of snails using the CMR (Capture-Mark-Recapture) method in four sections of the Biltongi-Narayanpara beel between August 2022 and February 2023. Snail samples were collected from four sampling sites, each located in different areas: one near agricultural land, one in the shallows, and one in the middle of the deepest part of the beel. The plot with the highest overall mean population density in terms of CMR for the presence of snails was plot 3 (33.25 ± 2.75), while the field with the lowest density was plot 4(22.75 ± 2.22). The biomass showed only slight variations across the different habitat categories. This is likely due to the presence of many young snails in shallow areas, whereas young snails in nearby regions were nearly nonexistent.